Boston - Grant, Kimberly (Lonely Planet guidebooks, 2000)
Featuring five original walking tours of the city neighbourhoods and details on Boston's hot spectator sports scene, this guide to the city also includes details of excursions along the New England coast and shopping trips to Maine.